Freshwater mussels in Italy: from no-name species and no-right species to useless regulation - Riccardi, Nicoletta (2019)
Any conservation management plan requires at the veiy least the following information: (l) clearly defined target species, and data on the species' (2) distribution and (3) population size. For European freshwater mussels this information is missing, deficient or outdated, and unevenly distributed among the different European countries. Paradoxically, the Southem European countries, more vulnerable to the impacts of climate change and water shortage, are those more poorly studied. Despite being recognized as a center of endemism and one of the major refugia of the glacial ages for several taxa, Italy is no exception. Information deficiencies result, at least in part, from objective difficulties, ex. taxonomic uncertainties and misidentifications. Thcsc latter affect both the legislation and the aUocation offunds, which are stricüy interdependent. Two Italian examples will be used to illustrate a paradox that practically hinders both the acquisition of information and, a fortiori, possible conservation actions: l) a "new" species that will not be included in the inventory or protected until the legislative bureaucratic procedure hás taken its course; 2) an "old" species that will become exünct without any conservation plan, because it appears only in the Annex V of the European Directive. Unfortunately, these two examples represent only the tip of the iceberg; underneath there are many legislative inconsistencies that contribute to forming a "cultural threat". A scaling up from the Italian to the European levei shows a further "threat": triggered by funding limitations, the growing spread of data-sharing infrastructures amplifies "errors" (e. g. mis-identifications). Like in avicious circle, species are going lost whüe the few resources still avaüable are absorbed to "capitalize" on already existing, mostly inadequate, knowledge.